Рекомендаційна система продуктів з використанням графових нейронних мереж - Лаврик , Юліана Олегівна (Національний університет “Львівська політехніка”, 2023)
Магістерська кваліфікаційна робота виконана студенткою групи КНСШ-22 Лаврик Юліаною Олегівною. Тема “Рекомендаційна система продуктів з використанням графових нейронних мереж”. Робота направлена на здобуття ступеня магістр за спеціальністю 122 «Комп’ютерні науки». Об’єктом дослідження є процеси підбору товарів, в яких найбільш зацікавлений користувач. Предметом досліджень є методи побудови систем рекомендацій товарів на основі графових нейронних мереж. Метою роботи є підвищення ефективності процесу рекомендації товарів, розробляючи алгоритм з використанням графових нейронних мереж, що надасть можливість розробити оперативну та якісну систему для рекомендації товарів. Для досягнення такої мети проводиться аналіз існуючих підходів до розробки систем рекомендацій та переваг використання графових нейронних мереж над іншими, дослідження алгоритмів побудови таких мереж та формування власної моделі з подальшою оцінкою її якості за допомогою різних спеціалізованих метрик. В результаті виконання дипломної роботи було розроблено рекомендаційну систему, що працює на основі графової нейронної мережі; розроблено її програмну реалізацію, яка дозволяє доповнювати та донавчати систему інформацією про нові товари для отримання рекомендацій інших категорій, а також коригувати набір гіперпараметрів для визначення оптимального набору для найбільш якісних результатів. Загальний обсяг роботи: 69 сторінок, 14 рисунків, 18 посилань. Master’s degree work of the student of the group CSAI-22 Lavryk Yuliana Olehivna. The topic is "Product Recommender System using Graph Neural Network". The work is aimed at obtaining a master's degree in 122 "Computer Science". The object of research is selection processes of products in which the user is the most interested. The subject of research is methods of building product recommendation systems based on the graph neural networks. The aim of the research is to increase the efficiency of the product recommendation process by developing an algorithm using graph neural networks, which will provide an opportunity to develop an operational and high-quality product recommendation system. To achieve this goal, the analysis of existing approaches to the development of recommendation systems and the advantages of using graph neural networks over others, the study of algorithms for building such networks and the developing of an own model with the subsequent evaluation of its quality using various specialized metrics are carried out. The modern world is developing and progressing very rapidly. Accordingly, there is an even greater amount of data that needs to be processed and analyzed. However, working with such volumes of data requires a large number of powerful resources that can provide not only high-quality, but also fast analysis. There is a lot of different information around, and it is necessary to develop and apply technologies that can effectively process it and highlight only what is useful for a particular user. One of the most effective such technologies is recommender systems. A recommender system is a system that, with the help of numerous machine learning methods, processes data about the user and the product he has chosen in order to provide the best possible personalized recommendations.
Product Recommender System using Graph Neural Network
Keywords: графова нейронна мережа (GNN), рекомендаційна система (RS), продукт, GraphSAGE, graph neural network (GNN), recommender system (RS), product, GraphSAGE